Working memory capacity in English monolingual and Afrikaans/English bilingual grade 1 learners. - Van Rooyen, Tahiti (My University, 2009)
Many learners in South Africa first encounter English when it is used as a medium of instruction at the start of formal schooling. This has ramifications for literacy acquisition and academic performance. Working memory is responsible for distributing cognitive resources among the various processing and storage tasks. It has been pivotal in many cognitive theories linking working memory to academic skills like reading comprehension and mathematics ability. In addition, research indicates that both Short Term Memory (STM) and Working Memory (WM) are instrumental in cognitive processing but that in bilinguals their roles are more complex than they are in monolinguals. This research explored the capacity of WM and the role of WM in reading comprehension and mathematical ability in two South African populations: a monolingual English group (L1) and a bilingual Afrikaans/English group (L2). No significant differences were found in the WM capacity of the two groups. In the second part of the study it was found that both reading comprehension and bilingualism depend on the same verbal domain resources of WM, which act as constraining factors for the L2 group. However, in the L1 group, there appeared to be less competition for verbal domain resources and more for visuospatial resources probably due to the phase of literacy acquisition these learners were in. In terms of WM and mathematical ability it was found that bilinguals exceed their storage capacity (STM) before they run out of processing capacity (WM). STM therefore is a constraining factor for this group. However, for the L1 group, visuospatial processing is the constraining factor. The research concludes that bilinguals use WM both for semantic processing of their nondominant language and for complex cognitive processing. While the WM capacity for monolingual and bilingual learners appears to be equivalent, the way the resources are allocated during cognitive tasks differ.
Keywords: Bilingualism; Working memory